Melatonin and Its Analogs for Prevention of Post-cardiac Surgery Delirium: A Systematic Review and Meta-Analysis - Han, Yunyang; Tian, Yu; Wu, Jie; Zhu, Xiaoqin; Wang, Wei; Zeng, Zhenhua; Qin, Zaisheng (Frontiers in Cardiovascular Medicine, 2022)
Background The effectiveness of melatonin and its analogs in preventing postoperative delirium (POD) following cardiac surgery is controversial. The purpose of this systematic review and meta-analysis was to confirm the benefits of melatonin and its analogs on delirium prevention in adults who underwent cardiac surgery. Methods We systematically searched the PubMed, Cochrane Library, Web of Science, Embase, and EBSCOhost databases, the last search was performed in October 2021 and repeated before publication. The controlled studies were included if investigated the impact of melatonin and its analogs on POD in adults who underwent cardiac surgery. The primary outcome was the incidence of delirium. The Stata statistical software 17.0 was used to perform this study. Results This meta-analysis included eight randomized controlled trials (RCTs) and two cohort studies with a total of 1,714 patients. The results showed that melatonin and ramelteon administration were associated with a significantly lower incidence of POD in adults who underwent cardiac surgery (odds ratio [OR], 0.46; 95% confidence interval [CI], 0.29–0.74; P = 0.001). The subgroup analyses confirmed that melatonin 3 mg (OR, 0.37; 95% CI, 0.18–0.76; P = 0.007) and 5 mg (OR, 0.34; 95% CI, 0.21–0.56; P < 0.001) significantly reduced the incidence of POD. Conclusion Melatonin at dosages of 5 and 3 mg considerably decreased the risk of delirium in adults who underwent cardiac surgery, according to our results. Cautious interpretation of our results is important owing to the modest number of studies included in this meta-analysis and the heterogeneity among them. Systematic Review Registration PROSPERO registration number: CRD42021246984.